Noise monitoring in the city of São Luís, Brazil - Santos, Diego Rosa dos; Silva, Sérgio Fernandes Saraiva da; Almeida, Will Ribamar Mendes; Santos, Airton Garcia da Silva; Araújo, Wilhamy Coimbra de; Villis, Paulo Cesar Mendes (Ciência e Natura, 2018)
The noise generated by vehicular traffic is a major source of discomfort for urban residents and directly affects their quality of life. This study performed the monitoring of urban noise in the city of São Luís, Brazil. The data were collected at 25 sampling points throughout the city over a period of 6 months—1 week per month from Monday to Sunday between the hours of 11:00 and 13:00. The results showed that 23 points were above the limits established by NBR 10151/00. The analysis of variance showed significant differences between the points. Therefore, it is evident that the population is exposed to high levels of noise capable of generating public health problems. The two points within the NBR limits were recorded in an area with dense vegetation, showing the importance of the preservation of the vegetation.